2021
DOI: 10.6018/reifop.470831
|View full text |Cite
|
Sign up to set email alerts
|

Cultura profesional y TIC en la formación del profesorado en tiempos de crisis: la percepción de los docentes

Abstract: En este artículo analizamos algunas razones básicas que explicarían las dificultades que el profesorado y los centros de Primaria han tenido para adaptarse a los cambios producidos por la pandemia. Para ello, nos basaremos en los resultados de dos investigaciones del grupo Stellae (USC). De la primera, utilizaremos los datos de las entrevistas a docentes de las Facultades de la USC que imparten la titulación de Magisterio, recogiendo sus percepciones sobre la construcción del conocimiento y la cultura profesio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
1
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
3
1
0
3
Order By: Relevance
“…The formulation of the challenges is complemented by the need for permanent technological and pedagogical support for teachers through training and support spaces that fundamentally favor the transition to current learning scenarios. The results of this study coincide with those of other authors [47][48], highlighting the lessons learned from virtual and hybrid learning models that have been implemented or strengthened to face the challenges of higher education in pandemic times. Higher education institutions must prioritize the active role of teachers in training to take on the challenges of research and pedagogical innovation in the digital world.…”
Section: Discussionsupporting
confidence: 86%
“…The formulation of the challenges is complemented by the need for permanent technological and pedagogical support for teachers through training and support spaces that fundamentally favor the transition to current learning scenarios. The results of this study coincide with those of other authors [47][48], highlighting the lessons learned from virtual and hybrid learning models that have been implemented or strengthened to face the challenges of higher education in pandemic times. Higher education institutions must prioritize the active role of teachers in training to take on the challenges of research and pedagogical innovation in the digital world.…”
Section: Discussionsupporting
confidence: 86%
“…In fact, this study has shown that primary school teachers in the BCAR have been overloaded with work due to the need to redesign and reorganise subjects, as shown by previous studies [16,17]. In this line, studies such as those by Álvarez-Núñez et al [45] and Hortigüela-Alcalá et al [46] highlight among the most relevant difficulties perceived by teachers in primary schools some of the conclusions derived from the present study. Among them, the following stand out: The digital gap between students from different social contexts; difficulties of VLEs when dealing with a large number of participations in a limited period of time; lack of support from the educational administration; lack of support and coordination of the center team and its teaching staff.…”
Section: Discussionsupporting
confidence: 62%
“…Al respecto, los participantes de esta investigación sostenían que las estrategias metodológicas de corte innovador como el flipped classroom, el aprendizaje cooperativo o la gamificación, promueven una capacitación holística del profesorado y la sensibilización para alcanzar una escuela y una sociedad comprometida con la educación inclusiva. Estos resultados son coincidentes con otros estudios (Álvarez-Núñez et al, 2021;Lara-Lara et al, 2023;Menjívar, 2017;Peralta-Lara y Guamán-Gómez, 2020;Rodríguez-Jiménez et al, 2019) en los que se expone cómo han de transformarse los procesos de formación docente mediante la aplicación de estrategias y recursos tecnológicos para hacer frente a los desafíos con los que se encuentran las escuelas del siglo XXI.…”
Section: Discusión Y Conclusionesunclassified